1956
DOI: 10.2118/536-g
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Water Flooding in the Presence of Free Gas

Abstract: Published in Petroleum Transactions, AIME, Volume 207, 1956, pages 215–221. Abstract Experimental studies covering a wide range of core materials and fluid properties have been conducted to determine the mechanism of oil displacement by water in a partially gas-saturated porous medium. In all instances, the presence of a gas phase was found to have a beneficial effect in reducing residual oil saturations. The practical significance of this benefit is discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 0 publications
2
18
0
1
Order By: Relevance
“…Conversely, as C moves to ∞, no NWF is residually trapped after imbibition. This purely empirical model was developed to describe observations in the literature of saturation hysteresis resulting from the entrapment of gas in water wet sandstone plugs after imbibition [ Kyte et al ., ; Holmgren and Morse , ]. Higher order empirical models, aimed at describing the more complex behaviour of mixed wetted and oil‐wet systems are also reported in the literature [e.g., Jerauld ; Spiteri et al ., ].…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, as C moves to ∞, no NWF is residually trapped after imbibition. This purely empirical model was developed to describe observations in the literature of saturation hysteresis resulting from the entrapment of gas in water wet sandstone plugs after imbibition [ Kyte et al ., ; Holmgren and Morse , ]. Higher order empirical models, aimed at describing the more complex behaviour of mixed wetted and oil‐wet systems are also reported in the literature [e.g., Jerauld ; Spiteri et al ., ].…”
Section: Resultsmentioning
confidence: 99%
“…Most relative permeability models that incorporate hysteresis (Jerauld 1997a;Killough 1976;Larsen and Skauge 1998;Lenhard and Parker 1987;Blunt 2000;Lenhard and Oostrom 1998) are based on it. It was developed to predict trapped gas saturation as a function of the initial gas saturation based on published experimental data from water-wet sandstone cores (Holmgren and Morse 1951;Kyte et al 1956;Dardaganian 1957).…”
Section: Development and Validation Of A New Model Of Relative Permeamentioning
confidence: 99%
“…Modeling of relative permeability is discussed in the following section. From early imbibition studies in gas-water and gas-oil systems (Holmgren and Morse, 1951;Dyes, 1954;Kyle et al, 1956;Crowell et al, 1966), and a single oil-water study (Pickell et al, 1966), all primarily conducted on sandstones, Land (1968Land ( , 1971 showed that S * gr increases with increasing S * gi following the relation:…”
Section: Resultsmentioning
confidence: 99%